Mapping Microbial Selves: Field Notes from a Dirty Parenting Project (Medicine Anthropology Theory, 2024)
Microbes exist everywhere on, in and around us. They are both ubiquitous and largely invisible, at least until they make their presence, or absence, felt. Recent years have seen a heightened sensitivity to microbial threats in the wake of the COVID-19 pandemic and widespread concerns about antimicrobial resistance (AMR) to antibiotics. At the same time, there is also a growing interest in the microbiome as a source of ‘wild immunology’. From this viewpoint, the human body is comprised of, embedded within, and dependent on its exposure to an ecosystem of microbes, and the absence of such exposure is linked to the development of auto-immune conditions such as Crohn’s disease and ulcerative colitis. Inspired by an emerging body of work in the humanities and social sciences which looks to engage with so-called lay knowledge and understandings of microbial forms (including bacteria, viruses, and fungi) and processes (such as contagion or digestion), this Field Note explores the piloting of ‘body mapping’ as a research method to engage with families to explore their collective understanding of their children’s microbiome.